Ubiquitin-specific peptidase 2 inhibits epithelial-mesenchymal transition in clear cell renal cell carcinoma metastasis by downregulating the NF-κB pathway. Issue 2 (1st February 2022) - Duan, Jiachen; Jin, Mengyuan; Yang, Dongjing; Shi, Jihua; Gao, Jie; Guo, Danfeng; Tang, Hongwei; Zhang, Shuijun; Qiao, Baoping
ABSTRACT: Clear cell renal cell carcinoma, the most common type of renal cancer, is associated with poor survival. Ubiquitin-specific peptidase 2 regulates the molecular mechanisms of cancer cells. However, its mechanism in clear cell renal cell carcinoma remains unclear. Quantitative real-time polymerase chain reaction, enzyme-linked immunosorbent assay, and immunohistochemistry were performed to assess ubiquitin-specific peptidase 2 expression in human clear cell renal cell carcinoma samples. Ubiquitin-specific peptidase 2 was weakly expressed in clear cell renal cell carcinoma samples and associated with poor patient outcomes. Ubiquitin-specific peptidase 2 inhibition promoted clear cell renal cell carcinoma cell proliferation, migration, and invasion. Ubiquitin-specific peptidase 2 overexpression inhibited clear cell renal cell carcinoma cell proliferation, migration, and invasion in vitro and in vivo . RNA-sequencing showed significant changes in the epithelial-mesenchymal transition-related pathways following ubiquitin-specific peptidase 2 knockdown. Western blotting was performed to detect the protein expression levels. Expression of p-nuclear factor-κB p65, N-cadherin, Vimentin, and Snail, which were markedly increased, as well as E-cadherin, which was decreased following ubiquitin-specific peptidase 2 knockdown. Rescue experiments using the nuclear factor-κB inhibitor BAY 11–7082 revealed that the migration and invasion abilities and the expression of epithelial-mesenchymal transition pathway proteins were inhibited in both the short hairpin RNA (shRNA) for ubiquitin-specific peptidase 2 and shRNA for negative control groups. Ubiquitin-specific peptidase 2 is a potential biomarker to distinguish clear cell renal cell carcinoma patients from healthy individuals. Ubiquitin-specific peptidase 2-mediated inhibition of epithelial-mesenchymal transition in clear cell renal cell carcinoma cells is dependent on the nuclear factor-κB pathway. Graphical abstract: uf0001